Role Model Pengelolaan Lembaga Pendidikan Islam Berbasis Prestasi di Madrasah Aliyah - Nur Alim; Syamsuddin Syamsuddin; Sitti Nurhalimah (STAI Hubbulwathan Duri, 2021)
This research aims to analyze the role model of achievement-based Islamic education management. This research is a type of descriptive qualitative conducted at Islamic Secondary School at Kendari, Southeast Sulawesi, Indonesia. The results of the research show that achievement-based management conducted by Islamic Secondary School at Kendari is divided into four stages. First, the planning stage by determining achievement targets, namely planning the activities to be carried out, looking at the race event, determining the coaching strategy and grouping students. Second, the stage of achievement-based student recruitment is the restriction of student quotas every year, special achievement pathways, academic tests, personality/ psychological tests and health tests. The stage of implementation of performance-based development through the construction of academic and non-academic fields as well as religious construction. The last stage is an achievement-based evaluation conducted via online, live review, parenting and PESONA (Week of Arts, Olympics and Sports) at the end of the year. Add the implication of the study here.